The Emerging Role of Cardiovascular Magnetic Resonance Imaging in the Evaluation of Metabolic Cardiomyopathies - Mavrogeni, S.; Markousis-Mavrogenis, G.; Markussis, V.; Kolovou, G. (Hormone and Metabolic Research, 2015)
The aim of this review is to discuss the role of Cardiovascular Magnetic Resonance (CMR) in the diagnosis, risk stratification, and follow-up of metabolic cardiomyopathies. The classification of myocardial diseases, proposed by WHO/ISFC task force, distinguished specific cardiomyopathies, caused by metabolic disorders, into 4 types: 1) endocrine disorders, 2) storage or infiltration disorders (amyloidosis, hemochromatosis and familial storage disorders), 3) nutritional disorders (Kwashiorkor, beri-beri, obesity, and alcohol), and 4) diabetic heart. Thyroid disease, pheochromocytoma, and growth hormone excess or deficiency may contribute to usually reversible dilated cardiomyopathy. Glucogen storage diseases can be presented with myopathy, liver, and heart failure. Lysosomal storage diseases can provoke cardiac hypertrophy, mimicking hypertrophic cardiomyopathy and arrhythmias. Hereditary hemochromatosis, an inherited disorder of iron metabolism, leads to tissue iron overload in different organs, including the heart. Cardiac amyloidosis is the result of amyloid deposition in the heart, formed from breakdown of normal or abnormal proteins that leads to increased heart stiffness, restrictive cardiomyopathy, and heart failure. Finally, nutritional disturbances and metabolic diseases, such as Kwashiorkor, beri-beri, obesity, alcohol consumption, and diabetes mellitus may also lead to severe cardiac dysfunction. CMR, through its capability to reliably assess anatomy, function, inflammation, rest-stress myocardial perfusion, myocardial fibrosis, aortic distensibility, iron and/or fat deposition can serve as an excellent tool for early diagnosis of heart involvement, risk stratification, treatment evaluation, and long term follow-up of patients with metabolic cardiomyopathies.
Keywords: metabolic cardiomyopathy; cardiovascular magnetic resonance imaging; endocrine disorders